Demanding Work : The Paradox of Job Quality in the Affluent Economy - Green, Francis (Book collections on Project MUSE., 2006)
In the last quarter century a vast number of jobs have been created in the affluent economies of the industrialised world. Economist Francis Green highlights contrasting trends, using quantitative indicators drawn from a series of social surveys and from administrative data.